A Prospective, Randomized, Blinded Study of Continuous Ropivacaine Infusion in the Median Sternotomy Incision Following Cardiac Surgery. Issue 2 (1st March 2013) - Agarwal, Shvetank; Nuttall, Gregory A.; Johnson, Michael E.; Hanson, Andrew C.; Oliver, William C.
Abstract : Objective: The aim of this prospective, randomized, double-blind, placebo controlled trial was to evaluate the safety and efficacy of continuous ropivacaine infusion of into the sternal wound. Methods: We planned to enroll 200 patients scheduled for various cardiac surgical procedures into the study. Patients, in a double-blind randomized fashion, were given either normal saline or 0.3% ropivacaine through 2 subcutaneous multiport catheters placed on either side of the sternal split at an infusion rate of 4 mL/h for 64 hours. The efficacy outcomes measured were time to extubation of the trachea, intensive care unit and hospital stay duration, pain scores, and narcotic usage. The safety outcomes measured were systemic local anesthetic toxicity, major cardiac complications, and wound infection. Measurements and Main Results: The data safety monitoring board stopped the study after enrolling 85 patients because of excessive sternal wound infections (9%, n = 44) in the ropivacaine group. This rate of infection was not statistically different from the control group (0%, n = 41, P = 0.12), but it was statistically different from our historical incidence of sternal wound infection (1.9%, no = 6381, P = 0.002). There was also a lack of evidence of efficacy for time to extubation of the trachea, narcotic usage, and pain control. Conclusions: The phase III trial did not show improvement in time to extubation of the trachea or pain control in the 0.3% ropivacaine group, but it was stopped early by the data safety monitoring board.